If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10s + 6 = 5 Reorder the terms: 6 + 10s = 5 Solving 6 + 10s = 5 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 10s = 5 + -6 Combine like terms: 6 + -6 = 0 0 + 10s = 5 + -6 10s = 5 + -6 Combine like terms: 5 + -6 = -1 10s = -1 Divide each side by '10'. s = -0.1 Simplifying s = -0.1
| 4x+34=12x-28 | | (k-2)x^2-2(k+3)x+k=0 | | 2x+50= | | 81^3t+7=(1/27)^-2t+8 | | 12x+28=6x-24 | | 3x.x=10 | | X^2+4x=7x+18 | | -7.3q+1.4=28.6-1.3q | | 6a/8-2a/12+7/2=7 | | 2340=13 | | 3r+27=0 | | -m/4+5/-6=7-6 | | 2x/9=6 | | 2x/9+2=4 | | 27x+49=-167 | | 1/-2+y=2/3 | | M^2+2m+1/m^2-2m-3=7 | | 10/-6 | | M^2+2m+1/m^2-2m-3=0 | | 56=42+u/11 | | 12+d/9=27 | | 4y-192=96 | | 9/-3-2x=9 | | -9-5x=-31 | | 6x-5x=45 | | (x+1)/5 | | -77-5x=-31 | | x^2+x+0.2925636=0 | | 13.04+x=28.96 | | 6(2x-5)-11x=8 | | 29-3x=2x+4 | | 13.04+x^5=28.96 |